Students’ Transitions Through English Medium Instruction Environment: A Kyrgyz Case - Eusafzai, Hamid Ali Khan (Frontiers in Education, 2022)
This qualitative exploratory research investigates Kyrgyz students’ transition experience in an English Medium Instruction (EMI) environment through the Multiple and Multi-dimensional Transition (MMT) theoretical lens. Data was collected from a small purposive sample of students through semi-structured interviews. The findings of the study reveal that the students experienced transitions in the academic, psychological, and social domains of their life. The academic transitions were in the form of gaining linguistic competencies, the psychological transitions were towards changing the students’ outlook and their image of self, and the social transitions were towards a readjustment of the students' role in their family and community. Thus, these mostly positive and multi-directional transitions were developmental and transformational.